An anthropological analysis of a skeletal material from Koziegłowy - Olińska, Krystyna (Anthropological Review, 1980)
The author describes skeletal remains of about 25 individuals whose mixed bones were excavated at a Halstatt Period site on Koziegłowskie Lake. Individual craniometric data are presented along with parameters of distributions of long bones measurements. The craniological series has been compared, by means of Penrose's method to other European cranial samples from the Halstatt Period. Results of this comparison are given in table 4.